1978
DOI: 10.1111/j.1365-3032.1978.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating behaviour in Oncopeltus fasciatus (Dallas): effects of diet, photoperiod, juvenoids and precocene II

Abstract: When adults of the large milkweed bug, Oncopeltus fasciatus (Dallas) were starved or fed non-host seeds, their mating activity during the 30 days following emergence was reduced by c. 50%. Topical applications of a juvenoid t o adults fed non-host seeds usually increased mating activity, sometimes to near the level of milkweed-fed controls. An optimal juvenoid dose applied to adults reared and fed on sunflower seeds increased mating activity by only 9% to 28% from that of controls reared and fed on milkweed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Precocenes-I and -II (7 methoxy-2,2-dimethylchromene and 6,7-dimethoxy-2,2-dimethylchromene, respectively) are chromene derivatives of plant origin (Bowers, 1976;Soderlund et al, 1980;Haunerland and Bowers, 1985) that have been shown to have multiple effects on metamorphosis during the pre-adult stages of different non-social insect species (Nemec et al, 1978;Unnithan and Nair, 1979;Kozhanova and Nemec, 1991;Khan and Kumar, 2000;Khan and Kumar, 2005;Gaur and Kumar, 2009) and on reproduction in adults of several insect orders where they prevent normal vitellogenic development of the oocytes, leading to sterility (Pratt and Bowers, 1977;Deb and Chakravorty, 1982;Bradley and Haynes, 1991;Kozhanova and Nemec, 1991;Kumar and Khan, 2004;Ringo et al, 2005;Amiri et al, 2010). In these non-social insect species, precocenes also affect several aspects of behavior such as aggression (Chen et al, 2005a), mating behavior (Walker, 1978), flight behavior (Rankin, 1980), maternal defensive behavior (Kight, 1998) and sexual behavior (Pathak and Bhandari, 2002;Ringo et al, 2005). In most cases the physiological, but not all the behavioral effects, were reversible by JH replacement therapy (Walker, 1978;Masner et al, 1979;Unnithan and Nair, 1979;Rankin, 1980;Li et al, 1993;Kight, 1998;Pathak and Bhandari, 2002;Chen et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precocenes-I and -II (7 methoxy-2,2-dimethylchromene and 6,7-dimethoxy-2,2-dimethylchromene, respectively) are chromene derivatives of plant origin (Bowers, 1976;Soderlund et al, 1980;Haunerland and Bowers, 1985) that have been shown to have multiple effects on metamorphosis during the pre-adult stages of different non-social insect species (Nemec et al, 1978;Unnithan and Nair, 1979;Kozhanova and Nemec, 1991;Khan and Kumar, 2000;Khan and Kumar, 2005;Gaur and Kumar, 2009) and on reproduction in adults of several insect orders where they prevent normal vitellogenic development of the oocytes, leading to sterility (Pratt and Bowers, 1977;Deb and Chakravorty, 1982;Bradley and Haynes, 1991;Kozhanova and Nemec, 1991;Kumar and Khan, 2004;Ringo et al, 2005;Amiri et al, 2010). In these non-social insect species, precocenes also affect several aspects of behavior such as aggression (Chen et al, 2005a), mating behavior (Walker, 1978), flight behavior (Rankin, 1980), maternal defensive behavior (Kight, 1998) and sexual behavior (Pathak and Bhandari, 2002;Ringo et al, 2005). In most cases the physiological, but not all the behavioral effects, were reversible by JH replacement therapy (Walker, 1978;Masner et al, 1979;Unnithan and Nair, 1979;Rankin, 1980;Li et al, 1993;Kight, 1998;Pathak and Bhandari, 2002;Chen et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…In these non-social insect species, precocenes also affect several aspects of behavior such as aggression (Chen et al, 2005a), mating behavior (Walker, 1978), flight behavior (Rankin, 1980), maternal defensive behavior (Kight, 1998) and sexual behavior (Pathak and Bhandari, 2002;Ringo et al, 2005). In most cases the physiological, but not all the behavioral effects, were reversible by JH replacement therapy (Walker, 1978;Masner et al, 1979;Unnithan and Nair, 1979;Rankin, 1980;Li et al, 1993;Kight, 1998;Pathak and Bhandari, 2002;Chen et al, 2005a). However, despite the plethora of species tested and abundant studies that were conducted using precocenes, only few have directly tested the change in JH titer post treatment (Pratt and Bowers, 1977;Sohn et al, 1991;Chen et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were demonstrated for the milkweed bug, Oncopelrus fusciatus. In this case, t h e feeding of non-host seeds (Walker, 1978) or milkweed buds and flowers (Ralph, 1976) reduces reproductive capacity. Similarly, Slansky ( 1980) found that decreasing food availability t o female 0. fuscialus by 75% prolongs longevity, delays t h e onset of egg production and increases the interclutch interval.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the effects of nutrient quality and quantity on the reproductive development of insects and related arthropods including mites (Henneberry, 1962;Cannon & Connell, 1965), aphids (van Emden, 1966;Dixon, 1970), orthopterans (Smith & Northcott, 1951;McCaffery, 1975), beetles (Latheef & Harcourt, 1972;Rankin & Rankin, 1980) and milkweed bugs (Ralph, 1976;Rankin & Riddiford, 1977;Walker, 1978;Slansky, 1980). An understanding of the role of nutrition in reproductive development is of major importance in the development of management strategies for the boll weevil, Anthonornus grandis (Boh.)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, precocenes affect several aspects of behavior in the non-social insect species, such as aggression (Chen et al, 2005a), mating behavior (Walker, 1978), flight behavior (Rankin, 1980), maternal defensive behavior (Kight, 1998) and sexual behavior (Pathak and Bhandari, 2002;Ringo et al, 2005). They inhibit the production of sex pheromone (Bowers, 1983).…”
Section: Multiple Effects Of Precocenesmentioning
confidence: 99%